Upgrade of the 4-rod radio frequency quadrupole for SARAF Phase II Linac. (1st August 2022) - Kaizer, B.; Barak, A.; Buzaglo, Y.; Dafna, H.; Farber, E.; Gavish, I.; Goldberger, N.; Kreisel, A.; Pami, H.; Perry, A.; Rodnizki, J.; Reinfeld, E.; et al.
Abstract: The 176 MHz 4-rod radiofrequency quadrupole (RFQ) is the crucial part of the Soreq Applied Research Accelerator Facility (SARAF) injector and must be able to operate at RF powers up to 190 kW continuous wave and transport 5 mA proton and deuteron beams. The SARAF Phase I RFQ is planned for use in Phase II. The period between the termination of Phase I and the installation of Phase II provided an opportunity to introduce RFQ improvements to fully meet the Phase II requirements. These upgrades and improvements are presented in this report together with the results of the recent conditioning campaigns.